Risk Management in the Field of Prevention of Healthcare Associated Urinary Tract Infections in the Context of Nursing Care - Krocová, Jitka; Prokešová, Radka (Verbum - vydavateľstvo Katolíckej univerzity v Ružomberku, 2018)
Urinary tract infections account for about one-third of healthcare-associated infections (HAI ). They most frequently occur in connection with an inserted urinary catheter. In this paper we focus on the prevention aspects of Catheter Associated Urinary Tract Infection (CAU TI) from a nursing point of view. The aim is also to present the results of a survey carried out through nursing care audits of a patient with an established urinary catheter. Material and methodology: The survey method was data processing from audits focused on care of patient’s with an inserted permanent urinary catheter. Audits were carried out in long-term care departments, 71 audits were performed in total. The research took place from March to May 2018. Results: By quantitative analysis of audit data, we evaluated the fulfilment of the nursing care standard for a patient with an inserted urinary catheter at a particular healthcare provider. Conclusion: the survey results revealed recommendations for a particular department concerning documentation management, a reassessment of indications for bladder catheterisation, and possibilities of change in catheter types and collection bags used. The survey has shown deficiencies in the care of collecting systems.
Keywords: Risk; Nursing care; Infection; Urinary tract; Prevention